Infected dentigerous cyst associated with a horizontal impacted ectopic supernumerary tooth induced by trauma to the maxillary incisors: A rare case report - Treville Pereira; Subraj Shetty; Amit Date (Journal of Medical Sciences, 2018)
Dentigerous cyst is known to be caused by the accumulation of fluid between the epithelium and the crown of an unerupted tooth. Its size increases by the expansion of the follicle, and it is attached to the neck of the tooth. These cysts are often associated with impacted third molars and maxillary canines and rarely with supernumerary teeth. In the present paper, we report a case of a dentigerous cyst associated with an impacted ectopic supernumerary tooth. This cyst was missed initially due to a failed root canal treatment associated with the nonvital maxillary central incisor. This case of a cystic lesion can create a dilemma between radicular and dentigerous cyst. The pathogenesis of the ectopic tooth, differential diagnosis, and management are also discussed.